Inflammation, lifestyle, and chronic disease : the silent link - Aggarwal, Bharat B., 1950-; Krishnan, Sunil; Guha, Sushovan (Boca Raton : CRC Press, 2012)
"Oxidative stress and inflammation are among the most important factors of disease. Chronic infections, obesity, alcohol and tobacco usage, radiation, environmental pollutants, and high-calorie diets have been recognized as major risk factors for a variety of chronic diseases from cancer to metabolic diseases. All these risk factors are linked to chronic diseases through inflammation. While short-term, acute inflammation generated by the immune system serves a therapeutic role, chronic low-level inflammation that may persist "silently" for decades is responsible for chronic diseases. Inflammation, Lifestyle, and Chronic Diseases: The Silent Link describes the role of dysregulated inflammation in persistent and recurring diseases. It investigates links to lifestyle and presents research on how the suppression of proinflammatory pathways may provide opportunities for both prevention and treatment of chronic diseases. The book covers neurodegenerative diseases, pulmonary diseases, asthma, rheumatic and arthritic diseases, skin disease, heart disease, chronic wounds, infectious disease, neuropsychiatric disorders such as depression, gastrointestinal diseases, insulin resistance, and cancer, many of which are also diseases of old age. For each chronic disease, contributors review the clinical and scientific literature and examine current and potential therapies, including conventional pharmacotherapies as well as natural products. Noting that the long-term use of steroids and nonsteroidal anti-inflammatory drugs (NSAIDs) can cause adverse side effects, many of the chapters address the role of dietary agents such as fruits, vegetables, legumes, pulses, nuts, and spices as ideal anti-inflammatory agents that can be consumed regularly. The book also suggests directions for further research. Clinical and science researchers, students, and health professionals interested in the link between inflammation, lifestyle, and chronic diseases will find this an informative resource"--Provided by publisher.
Roles of innate immunity and inflammation in the aging brain / Eitan Okun ... [et al.] -- Immune modulation of inflammation in neurodegenerative diseases : Alzheimer disease and amyotrophic lateral sclerosis / Michelle Mahanian ... [et al.] -- Environment and the role of inflammation in chronic pulmonary diseases : the silent mediator / Hongwei Yao and Irfan Rahman -- Role of inflammation and life style in chronic asthma / Eugene W.X. Ho ... [et al.] -- Role of inflammation in rheumatic diseases / Ali Mobasheri, Constance Aldinger, and Mehdi Shakibaei -- The role of inflammation in skin disease / Ricardo L. Berrios, Jigar R. Patel, Jack L. Arbiser -- Inflammation and heart diseases / Naveed A. Adoni, Ghassan H. Abusaid, and Ken Fujise -- Wound inflammation : from initiation to resolution / Sashwati Roy ... [et al.] -- Role of inflammation in infectious disease / Ian A. Clark and Lisa M. Alleva -- Implications of inflammation for neuropsychiatric disease : contributions and consequences / Thaddeus W.W. Pace, Charles L. Raison, Andrew H. Miller -- Role of inflammation in gastrointestinal diseases / Sarah Kraus ... [et al.] -- Pathogenesis of insulin resistance, the metabolic syndrome and inflammation : an issue of modern lifestyle / Paresh Dandona ... [et al.] -- Role of inflammation in cancer development / Muthu K. Shanmugam, Vinay Tergaonkar, and Gautam Sethi -- Chronic diseases caused by chronic inflammation requires chronic treatment : the anti-inflammatory style / Bharat B. Aggarwal ... [et al.].
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Inflammation -- Immunological aspects; Inflammation -- Pathophysiology; Chronic diseases -- Etiology; Diseases -- Causes and theories of causation; Electronic books